Ectopic Expression of Pumpkin NAC Transcription Factor CmNAC1 Improves Multiple Abiotic Stress Tolerance in Arabidopsis - Cao, Haishun; Wang, Li; Nawaz, Muhammad A.; Niu, Mengliang; Sun, Jingyu; Xie, Junjun; Kong, Qiusheng; Huang, Yuan; Cheng, Fei; Bie, Zhilong (Frontiers in Plant Science, 2017)
Drought, cold and salinity are the major environmental stresses that limit agricultural productivity. NAC transcription factors regulate the stress response in plants. Pumpkin (Cucurbita moschata) is an important cucurbit vegetable crop and it has strong resistance to abiotic stress; however, the biological functions of stress-related NAC genes in this crop are largely unknown. This study reports the function of CmNAC1, a stress-responsive pumpkin NAC domain protein. The CmNAC1-GFP fusion protein was transiently expressed in tobacco leaves for subcellular localization analysis, and we found that CmNAC1 is localized in the nucleus. Transactivation assay in yeast cells revealed that CmNAC1 functions as a transcription activator, and its transactivation domain is located in the C-terminus. CmNAC1 was ubiquitously expressed in different organs, and its transcript was induced by salinity, cold, dehydration, H2O2, and abscisic acid (ABA) treatment. Furthermore, the ectopic expression (EE) of CmNAC1 in Arabidopsis led to ABA hypersensitivity and enhanced tolerance to salinity, drought and cold stress. In addition, five ABA-responsive elements were enriched in CmNAC1 promoter. The CmNAC1-EE plants exhibited different root architecture, leaf morphology, and significantly high concentration of ABA compared with WT Arabidopsis under normal conditions. Our results indicated that CmNAC1 is a critical factor in ABA signaling pathways and it can be utilized in transgenic breeding to improve the abiotic stress tolerance of crops.